PTU-065 Serum lipid profile and kras mutation according to tumour location in metastatic colorectal cancer. (8th June 2018) - Tabuso, Maria; Arasaradnam, Ramesh
Abstract : Introduction: In metastatic colorectal cancer mutated Kirstin rat sarcoma viral oncogene (KRAS) and tumour location are predictive biomarkers of response to anti-epidermal growth factor receptor (EGFR) inhibition. KRAS protein activity requires specific binding to the lipid plasma membrane; the association between serum lipid profile and KRAS status has not so far been evaluated. Methods: A total of 201 patients with colorectal cancer stage IV, diagnosed between January 2012 and July 2017, were retrospectively analysed. Data including KRAS status, cancer location, total serum cholesterol, cholesterol:HDL ratio, LDL-cholesterol, HDL-cholesterol and tryglicerides were collected from clinical records. We used chi-square test to evaluate associations between serum lipid profile and KRAS status in stage IV colorectal cancer patients. Results: Out of 201 metastatic colorectal cancer patients 122 (60.69%) were males and 79 (39.30%) were females (mean age 65.38, standard deviation 11.39). Eighty-two (40.79%) patients exhibited KRAS mutation and 119 (59.20%) KRAS wild type. Ninety-five patients (47.26%) had cancer located at ascending colon, transverse colon and splenic flexure and 106 (52.73%) patients had cancer located at sigmoid colon and rectum. There was a significant association between KRAS mutation and high cholesterol:HDL ratio in colon cancer located at sigmoid colon and rectum [odds ratio (OR)=3.09, 95% confidence interval (CI) 1.3–7.0, p=0006], but not in colon cancer located at ascending colon, transverse colon and splenic flexure (OR=0.76, 95% CI 0.27–1.39, p=0.24). Conclusion: Our results reveal an association between high cholesterol:HDL ratio and KRAS mutation in sigmoid and rectal cancer. Specific tumour location and lipid profile may be useful in prognostic and predictive stratification of clinical outcomes.